POTRET KEPEMIMPINAN KIAI DAN PENGEMBANGAN NILAI-NILAI MULTIKULTURAL - Supriadi (Jurnal Manajemen Pendidikan Islam Darussalam (JMPID), 2023)
Leadership patterns have different nuances when in the midst of diversity. leadership has high articulation in dealing with multiple differences, especially the development of Islamic education in the midst of the Balinese Hindu Religion and Culture community. Leader patterns and policies are important in dealing with this reality. This study uses a qualitative approach with a case study type of research. Data were collected using in-depth interviews, participant observation, and documentation. Data analysis with Miles and Huberman's Interactive model: with steps; data reduction, data presentation, and conclusion/verification. Checking the validity of the data using source and method triangulation techniques, member checking, and discussions with colleagues. The results of this study are: (1) The leadership pattern of the Multicultural Kiai uses a contingency leadership pattern, namely a combination of eastern and democratic paternalistic leadership with a delegation style that has the characteristics of nurturing, protecting, educating, inclusive, tolerant, open communication style, guardian and controller. (2) The multicultural Kiai policy model with a modern management style that is based on missionary da'wah, and local wisdom, use a Double model, namely the Battom-up and top Down models or the Double policy model related to customary policies, curriculum development, Islamic Boarding School HR development policies and policies religious holidays.